Retno Kahuning Dance Learning to Increase the Character Educational Values of Students at Smp Penda Tawangmangu District, Karanganyar Regency - Endang Setyowati (Javanologi: International Journal of Javanese Studies, 2024)
Dance education opens up broad opportunities for freedom and development of students' creativity in the form of expression, creativity and appreciation activities. One of the greatest contributions of educational dance to human life is in emotional education, because in learning dance, apart from teaching knowledge, it also sharpens emotional sensitivity which will require students' motor skills to be included in character education. Retno Kahuning's basic dance movements show activeness and integrity when doing work. In the head movements in the dance, Retno Kahuning shows a view of life that leads to goodness, skillful hand movements show creativity,The Retno Kahuning dance can be used as a unifying bridge in people's lives, living side by side in achieving mutual prosperity. Meanwhile, character education can be instilled in students to understand the importance of developing attitudes of tolerance and mutual respect, respect for each other, and cooperation as a form of social harmony. Arts and culture education as a medium to develop appreciation, creativity and sensitivity